Adenocarcinoma coexisting with signet ring cell carcinoma in nonampullary duodenum - Lee, Tae Hoon; Wang, Joon Ho; Lee, Yun Hyeong; Ko, Soon Young; Ma, Chung Hyeon; Kim, Bohng Hee (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Lee TH, Wang JH, Lee YH, et al. Adenocarcinoma coexisting with signet ring cell carcinoma in nonampullary duodenum. Turk J Gastroenterol 2020; 31(3): 279-81.